2007
DOI: 10.1186/1472-6793-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory role of proteinase-activated receptor 1 in experimental bladder inflammation

Abstract: BackgroundIn general, inflammation plays a role in most bladder pathologies and represents a defense reaction to injury that often times is two edged. In particular, bladder neurogenic inflammation involves the participation of mast cells and sensory nerves. Increased mast cell numbers and tryptase release represent one of the prevalent etiologic theories for interstitial cystitis and other urinary bladder inflammatory conditions. The activity of mast cell-derived tryptase as well as thrombin is significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 78 publications
1
35
0
Order By: Relevance
“…Expression of PAR1-4 receptors has also been reported for an additional human urothelial cancer cell line (J82) however, receptor functionality was not investigated [21]. In the current study we document (using RT-PCR) expression of PAR receptors 1 through 4 in normal transformed human urothelial cells (UROtsa) [29], [30].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Expression of PAR1-4 receptors has also been reported for an additional human urothelial cancer cell line (J82) however, receptor functionality was not investigated [21]. In the current study we document (using RT-PCR) expression of PAR receptors 1 through 4 in normal transformed human urothelial cells (UROtsa) [29], [30].…”
Section: Discussionmentioning
confidence: 64%
“…Treatment with intravesical PAR1, PAR2 and PAR4 agonists induced inflammation in the mouse bladder [21]. Moreover, PAR1 receptors appear to mediate inflammation caused by a variety of inflammatory stimuli thus emphasizing their central role in the development of cystitis [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of inflammatory responses in wild type, PAR1- and PAR2-deficient mice, revealed a mandatory role of PAR1 and, to a lesser extent, PAR2 in mediating bladder responses to a variety of pro-inflammatory stimuli [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the "usual suspects" vascular and lymphatic endothelial cells are the target of VEGF signaling in many normal and diseased tissues, expression of VEGF receptors by bladder cancer cells (15,33) suggested that the situation might be different or, at least, more complex in this organ. To answer this question experimentally, we chose to use two different stimuli that have been proven to induce significant and reproducible bladder inflammation and alter VEGF signaling upon intravesical instillation, namely protease-activated receptors activating peptides (PAR-APs) (39,41) and BCG (37).…”
mentioning
confidence: 99%